The cost utility and budget impact of adjuvant racecadotril for acute diarrhea in children in Thailand - Rautenberg TA; Zerwes U (Dove Medical Press, 2017)
Tamlyn Anne Rautenberg,1,2 Ute Zerwes3 1IGES Institut, Berlin, Germany; 2Health Economics and HIV/AIDS Research Division (HEARD), School of Accounting, Economics and Finance, University of KwaZulu Natal, KwaZulu Natal, South Africa; 3Assessment in Medicine GmbH, Lörrach, Germany Objective: To evaluate the cost utility and the budget impact of adjuvant racecadotril for the treatment of acute diarrhea in children in Thailand. Methods: A cost utility model has been adapted to the context of Thailand to evaluate racecadotril plus oral rehydration solution (R+ORS) versus oral rehydration solution (ORS) alone for acute diarrhea in children <5 years old. The decision tree Excel model evaluates the costs and effects (quality-adjusted life years) over a 6-day time horizon from a public health care payer’s perspective in Thailand. Deterministic sensitivity analysis and budget impact analysis have been undertaken. Results: According to the cost utility model, the intervention (R+ORS) is less costly and more effective than the comparator (ORS) for the base case with a dominant incremental cost-effectiveness ratio of −2,481,390฿ for the intervention. According to the budget impact analysis (assuming an increase of 5% market share for R+ORS over 5 years), the year-on-year reduction for diarrhea as a percentage of the total health care expenditure is −0.0027%, resulting in potential net cost savings of −35,632,482฿ over 5 years. Conclusion: Subject to the assumptions and limitations of the models, adjuvant racecadotril versus ORS alone is potentially cost-effective for children in Thailand and uptake could translate into savings for the Thailand public health care system. Keywords: economic evaluation, cost utility, decision analysis, health technology assessment